Evidence in Civil Law - Austria - Nunner-Krautgasser, Bettina (Law & Society, 2015)
This report outlines the rules on the taking and using of evidence in Austrian civil procedure law. On the basis of principles such as the free disposition of parties, the attenuated inquisitorial principle or the principles of orality and directness, the judge and the parties form a "working group" when investigating the matter in dispute. The Austrian concept of an active judge, however, goes along with the judge's duty to do case-management and especially to induce a truthful fact-finding using judicial discretion. While only five means of proof (documents, witnesses, expert opinions, evidence by inspection and the examination of parties) are explicitly listed the Austrian civil procedure code, there is no numerus clausus regarding the means of evidence. Evidence may be freely assessed by the judge.